Urothelial Carcinomas of the Urinary Bladder With Plasmacytoid or Rhabdoid Features and Tendency of Epithelial-Mesenchymal Transition in 3 Dogs. Issue 5 (September 2018) - Lin, Susanne Je-Han; Kao, Chi-Fei; Wang, Fun-In; Jeng, Chian-Ren; Lee, Jih-Jong; Wang, Lei-Ya; Chang, Hui-Wen; Chen, Yi-Jiun; Liu, Chen-Hsuan; Pang, Victor Fei
Plasmacytoid and rhabdoid variants of urothelial carcinomas (UCs) of the urinary bladder have been described in humans with plasma cell–like or rhabdoid cellular appearance and aggressive clinical outcome. Canine UC of the bladder is generally classified as papillary/nonpapillary and infiltrating/noninfiltrating with limited information regarding other histological patterns. We report 3 cases of UC of the urinary bladder showing a unique discohesive cellular morphology with malignant behavior resembling the human plasmacytoid and rhabdoid variants of UC, which may raise some difficulties in diagnosis. Epithelial-mesenchymal transition and reduced E-cadherin expression were revealed by immunohistochemistry in 2 cases, possibly explaining the discohesive and invasive behavior of the tumor cells. The findings broaden the morphological spectrum as well as the distinct clinical features of canine UC of the urinary bladder.